2022
DOI: 10.3390/w14071033
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of Antibiotic Presence in Ebro River Basin (Spain): Identification of the Emission Sources

Abstract: Water monitoring is key to determining the presence of potentially hazardous substances related to urban activities and intensive farming. This research aimed to perform a long-term (four years) quantitative monitoring of selected antibiotics (azithromycin, enrofloxacin, trimethoprim and sulfadiazine) both in rivers and wastewaters belonging to the Ebro River basin (North of Spain). The target antibiotics were chosen on the basis of a preliminary multispecies screening. The analysis of the antibiotics was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Ciprofloxacin is the most commonly detected antibiotic in European groundwater, often found in high concentrations near pig farms and manure-spreading sites [66]. In fact, farms have been identified as the main source of ciprofloxacin and enrofloxacin in water [67]. Ciprofloxacin is highly soluble in water and mobile due to its hydrophilic nature.…”
Section: Analysis Of Groundwater Collected From the Vicinity Of The Farmmentioning
confidence: 99%
“…Ciprofloxacin is the most commonly detected antibiotic in European groundwater, often found in high concentrations near pig farms and manure-spreading sites [66]. In fact, farms have been identified as the main source of ciprofloxacin and enrofloxacin in water [67]. Ciprofloxacin is highly soluble in water and mobile due to its hydrophilic nature.…”
Section: Analysis Of Groundwater Collected From the Vicinity Of The Farmmentioning
confidence: 99%
“…However, their increasing use and misuse has led to the generation of antibiotic-resistant bacteria and environmental pollution (Chen et al, 2021;Cacace et al, 2019). Antibiotics and their degradation products have been frequently detected in aquatic environments, including rivers, lakes, and wastewater treatment plants, posing significant threats to aquatic ecosystems and public health (Barbosa et al, 2016; POCTEFA territory (Moles et al, 2022;López-Serna et al, 2011). In this specific region, which has significant intensive farming (Moles et al, 2022), the highest frequency of detection in wastewater has been observed for azithromycin (detected in 92% of the samples), sulfamethoxazole (92%), trimethoprim (75%), ciprofloxacin (75%), and enrofloxacin (61%) (Moles et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For the first issue, the scientific community is required. In this regard, in recent years, many authors [8][9][10] have developed specific analytical methodologies for the presence of certain CECs in environmental matrices, as well as guidelines for risk analysis in different environmental compartments, life cycle studies, etc.…”
Section: Introductionmentioning
confidence: 99%